Competitiveness of Polish mid-tech and high-tech exports to the European Union (EU-27) in the first decade of the 21st century - Michalski, Bartosz (Economics and Business Review, 2014)
The paper addresses the issue of structural changes in Polish exports to the European Union (EU-27) in the period 2001-2011 in terms of the revealed comparative advantages (RCA) and technological intensity (shifts in shares of mid-tech and high-tech industries) taking into account the context of the growing openness of the Polish economy and the substantial orientation to European markets. The principal aim of the research is thus an empirical examination by making use of trade data on the 4-digit level of desaggregation of the Harmonised System and whether the technological intensity of Polish exports was consistent with the evolution of comparative advantages and which of the mid-tech and high-tech sectors became the biggest winners (also losers) in the integration processes within the European common market. The results suggest a strong dependency of Polish mid-tech and high-tech exports to the EU-27 on the activity of foreign investors (multinational companies) and their technologies being transferred to Poland. (original abstract)